Commercial centralities and fairs in the northwest of the Metropolitan Region of Buenos Aires - Vecslir, Lorena (2023)
The analysis of centralities represents an entry point to metropolitan space-time dynamics, with multiple variants in terms of typologies, urban articulations, access modes, commercial profiles, and land uses. In the case of the Metropolitan Region of Buenos Aires, from the hypothesis that there are tacit networks of exchange and commerce that are juxtaposed territorially and temporally, shaping centralities with different orders of insertion and metropolitan behavior, this article delves into the relationships established between traditional street commerce and temporary consumption patterns, such as fairs and markets. Based on the use of open data platforms and information mapping, documentary research techniques, direct observation, and interviews with key informants, we analyze the structure of centralities in two municipalities of the metropolitan northwestern first ring (San Miguel and San Martin), emphasizing the temporal modalities of commercial use, and we characterize the typologies of fairs using four representative cases. By way of conclusion, a reflection is made on the competitive and complementary relations among the different commercial formats.